Probing BEC phase fluctuations with atomic quantum dots - Bruderer, M; Jaksch, D (2006)
We consider the dephasing of two internal states |0〉 and |1〉 of a trapped impurity atom, a so-called atomic quantum dot (AQD), where only state 1〉 couples to a Bose-Einstein condensate (BEC). A direct relation between the dephasing of the internal states of the AQD and the temporal phase fluctuations of the BEC is established. Based on this relation we suggest a scheme to probe BEC phase fluctuations non-destructively via dephasing measurements of the AQD. In particular, the scheme allows to trace the dependence of the phase fluctuations on the trapping geometry of the BEC. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.